2017
DOI: 10.1128/mbio.01068-17
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Prioritization to Dietary Glycans by Gut Bacteria in a Competitive Environment Promotes Stable Coexistence

Abstract: When presented with nutrient mixtures, several human gut Bacteroides species exhibit hierarchical utilization of glycans through a phenomenon that resembles catabolite repression. However, it is unclear how closely these observed physiological changes, often measured by altered transcription of glycan utilization genes, mirror actual glycan depletion. To understand the glycan prioritization strategies of two closely related human gut symbionts, Bacteroides ovatus and Bacteroides thetaiotaomicron, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 47 publications
4
106
0
1
Order By: Relevance
“…The competitive interactions summarized in these tables are just starting to be explored experimentally. In fact, the first experimental results relevant to communities within the human gut have already been reported [61,54]. Specifically, these results demonstrate the preferences and competitive abilities of 2 Bacteroides species for 9 particular polysaccharides.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The competitive interactions summarized in these tables are just starting to be explored experimentally. In fact, the first experimental results relevant to communities within the human gut have already been reported [61,54]. Specifically, these results demonstrate the preferences and competitive abilities of 2 Bacteroides species for 9 particular polysaccharides.…”
Section: Discussionmentioning
confidence: 63%
“…Recent work by Martens and collaborators [61,55,40] has established that many species in Bacteroides (the most prevalent genus in the human gut microbiome [51,12]) exhibit this kind of preferential nutrient utilization -with respect to polysaccharides present in a typical diet [20]. Interestingly, even species such as B. ovatus and B. thetaiotaomicron -which are closely-related evolutionarily -display rather different polysaccharide preference hierarchies [61].…”
Section: Introductionmentioning
confidence: 99%
“…2016). For example, previous studies have demonstrated that bacteria can show diet preference between different dietary glycans, which can prolong species coexistence in co-cultures (Tuncil et al 2017). Such dietary preference might leave some resources less utilised, providing an opportunity for invasion (Tilman 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The glycan-foraging capability could enhance the bacterial fitness and colonisation in the infant gut (Martens et al 2008) and the finestructure prioritisation at species level has been accounted for the collective fitness of Bacteroides spp. (Tuncil et al 2017). As such, several HMOS structures including 2'-FL, LNFP I, and LDFT were found to correlate positively with the abundance of Bacteroides spp.…”
Section: Differential D-and L-lactate Metabolism By Gut Commensalsmentioning
confidence: 82%